Phosphate recovery from sewage sludge supernatants using magnetic nanoparticles - Gulyas, Anett (My University, 2019)
Fosfor en temel besinlerden biridir, gübrelerin, deterjanların ve cilaların üretiminde kul-lanılır. Aşırı besin boşalmasından kaynaklanan çevre kirliliği, atık su arıtımında en önemli konudur. Besinler, yüzey suyu kaynakları, yeraltı suyu ve toprak üzerinde birçok olum-suz etki yaratır. Fosforun farklı sektörlerde yaygın olarak kullanılmasına rağmen, fosfor yenilenemez ve değiştirilemez sınırlı bir kaynaktır. Sonuç olarak, fosfatın geri kazanımı, uzaklaştırmanın yanı sıra dikkate alınmalıdır.Bu çalışma, kanalizasyon çamuru süpernatanından fosfor gideriminde manyetik nano-parçacıkların (MNP'ler) kullanılmasının etkinliğini araştırmak için yapılmıştır. Çalışma kapsamında farklı parametrelerin demir oksit manyetik nanoparçacıkların kullanılmasıyla fosfat adsorpsiyonu üzerine etkilerini araştırmak için toplu deneyler yapıldı.Demir oksit MNP birlikte çökeltme yöntemiyle hazırlanmıştır. MNP karakterizasyonu, X-ışını kırınımı, Taramalı Elektron Mikroskobu ve Fourier Transform İnfrared Spektros-kopi ölçümleri ile yapıldı. Bu deneyler demir oksit MNP'nin etkili fosfat adsorpsiyonunu kanıtladı. Manyetik nanopartiküllerin yüzeyinde fosforun adsorbe olduğu varlığı, enerji dağıtıcı x-ışını spektroskopisi kullanılarak doğrulanmıştır. Partiküllerin yüzey yükünü farklı pH değerlerinde belirlemek için Zeta potansiyel ölçümleri yapılmıştır.Denge çalışmaları, sentetik P çözeltisinin ve süpernatan çözeltisinin Redlich-Peterson izoterm modeliyle tutarlı olduğunu gösterdi. Sips modeli kullanılarak hesaplanan demir oksit MNP'nin teorik maksimum adsorpsiyon kapasitesi 20.8 mg / g'dir. Sentetik fosfat çözeltisinin ve süpernatan çözeltisinin kinetik çalışmaları, Elovich modeliyle tutarlıydı. En yüksek adsorpsiyon kapasitesi, 1000 mg/ L P çözeltisi ve 0.3 g manyetik nanoparti-küller ile ölçülmüştür. Fosforun demir oksit MNP yüzeyinden desorpsiyonu, MNP'lerin 1 saat boyunca 1 M NaOH çözeltisi ile işlenmesiyle etkili bir şekilde yapıldı.Bu çalışmanın amacı, fosfatın adsorpsiyonu için MNP'yi değerlendirmektir. Fosfat geri kazanımı için daha ucuz ve daha uygun bir yöntemi incelemek için nanopartiküller için daha doğru bir kullanım bulmak istiyoruz.

Phosphorus is one of the most essential nutrients; it is used in the manufacture of ferti-liz¬ers, detergents, and polishers. Environmental pollution due excessive nutrient dis-charges is the most important issue in wastewater treatment. Nutrients have many ad-verse effects on surface water resources, groundwater and soil. Despite the extensive uses of phosphorus in different sectors, phosphorus is a non-renewable and non-interchangea¬ble limited resource. Consequently, the recovery of phosphate should be consi¬dered as well as the removal.This study was carried out to investigate the efficiency of employing magnetic nanopar-ticles (MNPs) in phosphorus removal from sewage sludge supernatant. In the scope of the study, batch experiments were performed to investigate the effect of different pa-rameters on phosphate adsorption using iron oxide magnetic nanopar¬ticles.The iron oxide MNP was prepared with co-precipitation method. MNP characterization was done with X-ray diffraction, Scanning Electron Microscopy and Fourier Transform Infrared Spectroscopy measurements. These experiments proved the effective phosphate adsorption by iron oxide MNP. The presence adsorbed of the phosphorus on the surface of magnetic nanoparticles was con¬firmed using energy-dispersive x-ray spectroscopy. Zeta potential measurements were conducted to determine the surface charge of the particles at different pH values. Equilibrium studies showed that the synthetic P solution and supernatant solution was consistent with the Redlich-Peterson isotherm model. The theoretical maximum adsorp-tion capacity of iron oxide MNP calculated using Sips model is 20.8 mg/ g. The kinetics studies of the synthetic phosphate solution and supernatant solution was consistent with the Elovich model. The highest adsorption capacity was measured with 1000 mg/ L P solution and 0.3 g magnetic nanoparticles. Desorption of phosphorus from the iron oxide MNP surface was effectively done by treating the MNPs with 1 M NaOH solution for 1 hour. The aim of this study to evaluate the MNP for the adsorption of phosphate. We would like to find a more accurate usage for nanoparticles, moreover to examine a cheaper, more available method for phosphate recovery. CONTENTSACKNOWLEDGEMENT3ÖZETIIIABSTRACTVSYMBOLSVIIABBREVIATIONSIXLIST OF FIGURESXLIST OF TABLESXII1.INTRODUCTION11.1.PHOSPHORUS AND PHOSPHATE11.1.1.IMPORTANCE OF PHOSPHORUS11.1.2.Harms Related to Phosphate21.1.3.Phosphorus Removal Technologies21.1.3.1.Physical removal21.1.3.2.Enhanced biological phosphorus removal (EBPR)21.1.3.3.Chemical treatment31.2.ADSORPTION41.2.1.Adsorption process41.2.2.P removal by adsorption51.3.DESORPTION/ RECOVERY61.4.ABOUT NANOTECHNOLOGY IN GENERAL71.4.1.Nanomaterial81.4.1.1.Classification of NM91.4.1.2.Synthesis methods of NP101.4.1.3.Characterization methods111.4.2.Magnetic nanoparticles112.MATERIALS AND METHODS142.1.MATERIALS142.1.1.Synthetic P solution142.1.2.Dewatered Sludge Supernatant142.2.METHODS142.2.1.Synthesis of Magnetic Nanoparticles142.2.2.Physicochemical characterization of Fe3O4172.2.3.Adsorption experiments192.2.4.Desorption experiments222.2.5.Analytical methods232.2.6.Validation of kinetic and isotherm models243.RESULTS AND DISCUSSION253.1.CHARACTERIZATION OF THE ADSORBENT253.1.1.Point of zero charge253.1.2.FT-IR results263.1.3.XRD results303.1.4.SEM results313.1.5.EDX results323.2.ADSORPTION PERFORMANCE323.2.1.Effect of P concentration – equilibrium tests323.2.2.Kinetic analysis373.2.3.Effect of adsorbent dosage403.2.4.Effect of pH413.2.4.1.Adsorption of NH4-N423.3.DESORPTION EXPERIMENTS433.3.1.Desorption of NH4-N484.CONCLUSIONS49REFERENCES51ÖZGEÇMİŞ63
Keywords: Adsorpsiyon; Adsorption; Çevre bilimi; Environmental sciences; Fosfat geri kazanımı; Fosfat giderimi; Manyetik nanopartiküller; Phosphate recovery; Phosphate removal; Zeta po-tansiyeli : Magnetic nanoparticles; Zeta potential